Consequences of changing regional integration on environmental development, agricultural markets, and food security - L.A. Omarbakiyev; S.M. Kantarbayeva; A.K. Nizamdinova; S.T. Zhumasheva; G.Zh. Seitkhamzina; A. Saulembekova (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Geopolitical risks have made significant changes in the integration ties between the countries of Central Asia, which has affected the sustainable development of the agro-industrial complex and food security. The adoption of urgent measures to improve food security, on the one hand, is a necessary condition for the development of the Republic of Kazakhstan, but on the other hand, it can lead to a decrease in the level of environmental security in the country if the possible consequences in the reintegration process are not considered. Therefore, this article aimed to examine the sustainable agriculture practices implemented in Kazakhstan’s agro-industrial complex to improve food security and reduce the environmental impact of agriculture.METHODS: To collect information, a mixed research strategy combining qualitative and quantitative methods was used. The collection of information was carried out in the summer of 2022 and consisted of three stages. In the first stage, statistical information was collected; in the second stage, a correlation analysis was carried out; and in the third stage, a survey of 40 experts was conducted.FINDING: The data obtained indicate that the efficiency of Kazakhstan’s agricultural production strongly and directly depends on the level of the country’s integration into the united Eurasian Economic Union market. Due to the geographical features of Kazakhstan’s location, it is necessary to develop areas that are primarily focused on the internal capabilities of the country. Internal changes will help the industry increase international competitiveness and efficiency while promoting sustainable development and ensuring food security and environmental safety.CONCLUSION: The article determined that it is necessary to prioritize developing multilateral partnerships to address transportation and logistics challenges in the export and import of agricultural products, and reduce dependence on the import of seeds, breeding products, fodder, and agricultural machinery. However, to effectively promote these areas, it is necessary to improve food security through the introduction of sustainable agriculture practices, such as crop diversification, conservation agriculture, integrated pest management, and drip irrigation.